Brazilian gutta-percha points. Part II: thermal properties Cones nacionais de guta-percha. Parte II: propriedades térmicas - Cláudio Maniglia-Ferreira; Eduardo Diogo Gurgel-Filho; João Batista Araújo Silva Jr; Regina Célia Monteiro de Paula; Judith Pessoa Andrade Feitosa; Brenda Paula Figueiredo de Almeida Gomes; Francisco José de Souza-Filho (Sociedade Brasileira de Pesquisa Odontológica, 2007)
This study was undertaken to explore the effect of heating on gutta-percha, analyzing the occurrence of endothermic peaks corresponding to the transformation that occurs in the crystalline structure of the polymer during thermal manipulation. This study also seeked to determine the temperature at which these peaks occur, causing a transformation from the beta- to the alpha-form, and from the alpha- to the amorphous phase. Eight nonstandardized gutta-percha points commercially available in Brazil (Konne, Tanari, Endopoint, Odous, Dentsply 0.04, Dentsply 0.06, Dentsply TP, Dentsply FM) and pure gutta-percha (control) were analysed using differential scanning calorimetry (DSC) and thermogravimetry analysis (TGA). The transition temperatures were determined and analysed. With the exception of Dentsply 0.04 and Dentsply 0.06, the majority of the products showed thermal behaviour typical of beta-gutta-percha, with two endothermic peaks, exhibiting two crystalline transformations upon heating from ambient temperature to 130°. Upon cooling and reheating, few samples presented two endothermic peaks. It was concluded that heating dental gutta-percha to 130°C causes changes to its chemical structure which permanently alter its physical properties. Este estudo teve como objetivo analisar, através da Calorimetria Diferencial de Varredura (DSC) e Análise Termogravimétrica (TGA), os efeitos do aquecimento sobre o polímero guta-percha, bem como explorar a ocorrência de picos endotérmicos, os quais correspondem às transformações cristalinas do polímero guta-percha, o que é traduzido em transições de fases (fase beta para alfa e fase alfa para amorfa). Foram utilizadas 8 marcas comerciais de cones de guta-percha não-estandardizados disponíveis no mercado brasileiro (Konne, Tanari, Endopoint, Odous, Dentsply 0.04, Dentsply 0.06, Dentsply TP, Dentsply FM), além da guta-percha pura (controle). As temperaturas de transição foram determinadas e analisadas. Com exceção das amostras Dentsply 0.04 e Dentsply 0.06, todas as demais apresentaram duas transformações cristalinas de fase quando submetidas ao aquecimento da temperatura ambiente até 130°C, comportamento típico de guta-percha em fase beta. Ao serem resfriadas e reaquecidas, poucas amostras apresentaram dois picos endotérmicos. É possível concluir que o aquecimento a 130°C causa danos na estrutura química do polímero guta-percha, o qual altera de forma definitiva suas propriedades físicas.